Determinants of the Financial Behavior of Universitas Terbuka Students at SALUT Kartini Rembang - Durrotun Nafisah; Dian Anita Sari (Manunggal Halim Jaya, 2026)
This study examines the influence of hedonistic lifestyle, financial technology, and financial literacy on the financial behavior of students in the Management Study Program at Open University SALUT Kartini Rembang. Data were collected using a questionnaire and a proportional random sampling technique. The data were analyzed using multiple linear regression with IBM SPSS Statistics (version 25). The results indicate that financial literacy and financial technology significantly and positively affect the financial behavior of students in the Management Study Program at Open University SALUT Kartini Rembang. Meanwhile, a hedonistic lifestyle has a negative but relatively weak effect on students' financial behavior. The coefficient of determination (R²) shows that 16.7% of the variation in financial behavior can be explained by the variables included in the model, while the remaining 83.3% is influenced by other factors not examined in this study.